An Integrated Water Management Plan (IWRMP) for Oman using an Expert System Technique - Kabbashi, Nassereldeen; Muyibi, Suleyman Aremu (Nova Science Publishers, 2009)
Provision of water, food, energy, and shelter throughout the world were integrated with bio-systems and was a sustainable approach for the management of organic wastes as well as in the past. Increased urbanization an dependence on mechanical technologies coupled with lifestyle changes and market driven economic centralism is consuming resources in unsustainable ways. This urban-lifestyle and commercial activity is often unconnected with surrounding ecosystems and bio-systems. In questioning the sustainability of lifestyle and commercial activities old approaches have been reassessed and refined. Development of decentralised technologies that mimic bio-systems have led to real commercial gains without sacrificing a sustainable approach. Decentralised approa-systems guarantee innovation. The use of bio-systems and models derived from them can have real benefit to the environment and to the economy. The papers in this book will be of interest to academics, industries, policy makers and community workers who are worrying on several aspects of utilising bio-systems and making it sustainable. The topics discussed in this book are mainly on the technologies related to the management of bio-systems.